The Dynamic Reactance Interaction – How Vested Interests Affect People’s Experience, Behavior, and Cognition in Social Interactions - Steindl, Christina; Jonas, Eva (Frontiers in Psychology, 2015)
In social interactions, individuals may sometimes pursue their own interests at the expense of their interaction partner. Such self-interested behaviors impose a threat to the interaction partner’s freedom to act. The current article investigates this threat in the context of interdependence and reactance theory. We explore how vested interests influence reactance process stages of an advisor-client interaction. We aim to explore the interactional process that evolves. In two studies, participants took the perspective of a doctor (advisor) or a patient (client). In both studies we incorporated a vested interest. In Study 1 (N=82) we found that in response to a vested interest of their interaction partner, patients indicated a stronger experience of reactance, more aggressive behavioral intentions, and more biased cognitions than doctors. A serial multiple mediation revealed that a vested interest engendered mistrust toward the interaction partner and this mistrust led to an emerging reactance process. Study 2 (N=207) further demonstrated that doctors expressed their reactance in a subtle way: They revealed a classic confirmation bias when searching for additional information on their preliminary decision preference, indicating stronger defense motivation. We discuss how these findings can help us to understand how social interactions develop dynamically.